2019
DOI: 10.3892/etm.2019.8032
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑139‑5p regulates chronic inflammation by suppressing nuclear factor‑κB activity to inhibit cell proliferation and invasion in colorectal cancer

Abstract: The inflammatory microenvironment, which mediates the initiation and malignant development of tumors, has been reported to be associated with microRNA (miRNA) dysregulation. In the present study, the expression of miR-139-5p was analyzed in colorectal cancer (CRC) cell lines SW480, HT29, HCT-8, LoVo and HCT116, aiming to investigate the function and mechanism of miR-139-5p in the regulation of the malignant phenotypes of CRC. miR-139-5p expression was found to be considerably downregulated in CRC cell lines co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 43 publications
(45 reference statements)
2
17
0
Order By: Relevance
“…34 Furthermore, a recent study has revealed that overexpressed miR-139-5p reduces the inflammatory cytokines expression. 36 The observation of the study was that reduced EZH2 or elevated miR-139-5p accelerated cell proliferation and suppressed apoptosis of HASMCs, restrained oxidative stress and cell apoptosis in arterial tissues of mice with AS. This finding is also reported by Zhang et al that repressive EZH2 also inhibits the progression of lung injury by declining the pulmonary cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…34 Furthermore, a recent study has revealed that overexpressed miR-139-5p reduces the inflammatory cytokines expression. 36 The observation of the study was that reduced EZH2 or elevated miR-139-5p accelerated cell proliferation and suppressed apoptosis of HASMCs, restrained oxidative stress and cell apoptosis in arterial tissues of mice with AS. This finding is also reported by Zhang et al that repressive EZH2 also inhibits the progression of lung injury by declining the pulmonary cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…37 Moreover, the finding is persistent with that of Zhu et al who demonstrates that excessive miR-139-5p in colon cancer cell lines obviously suppresses the cell proliferation in vitro and in vivo. 36 Another study has elucidated that all types of gain-of-function assays exhibits that the up-regulated miR-139-5p represses cell proliferation and induces cell apoptosis. 38 In conclusion, our study offers evidence that downregulated EZH2 or elevated miR-139-5p inhibits ox-LDLinduced HASMCs apoptosis, plaque formation and inflammatory response in AS mice, which may be related to down-regulated STAT1.…”
Section: Discussionmentioning
confidence: 99%
“…Among these, AREG, is associated with various types of cancers and inflammatory conditions [61]. Proto-oncogene c-MET, VEGFA, CXCL3 and MMP9, which appear to play roles in CRC biology and immune function [62][63][64] are also up regulated.…”
Section: Discussionmentioning
confidence: 99%
“…The final visualization of the heat map was obtained based on the intensity of the fold-charge evaluated (Figure 3). The articles that we have been using for this part of our work covered the following topics: brain injury [25,26], inflammatory mechanism [27][28][29][30][31][32], and cancer [33][34][35][36][37]. The specifications of papers included in these analyses are reported in Table 1. 2.10.…”
Section: Determination Of Cytosol Concentration Of Mmp9mentioning
confidence: 99%